Surgical treatment of patients with multiple brain metastases - D. M. Belov; V. B. Karakhan; A. Kh. Bekyashev; E. V. Mitrofanov; E. V. Prozorenko; V. A. Aleshin; R. A. Sufianov; D. R. Nashletashvili (Опухоли головы и шеи, 2024)
Introduction. The standard of treatment for patients with single cerebral metastases is surgery and radiosurgery. The use of these methods significantly increases survival rates.Aim. To compare the results of surgical treatment of patients with single and multiple cerebral metastases.Materials and methods. The study included 40 patients with single and multiple cerebral metastases who underwent neurosurgical intervention in the neuro-oncology department of the N.N. Blokhin National Medical Oncology Research Center from 2010 to 2022.Results. All patients are divided into 3 groups. Group A included 15 patients who removed all available cerebral foci (from 2 to 4). Group B included 10 patients with multiple cerebral metastases who underwent removal of one symptomatic metastasis. In group C, 15 patients who underwent removal of a single metastasis. It was noted that the survival of patients after removal of all cerebral metastases is identical to the survival of patients after removal of single metastasis 11.9 and 12.4 months, respectively. And it was significantly higher than the survival of patients who removed not all cerebral metastases 6.2 months (p = 0.03). Also in group A and C, the percentage of local relapses was identical. Improvement in neurological status was noted in all groups, there was only an increase in cognitive-mnestic disorders in group A, where all cerebral foci were removed. However, these disorders were moderate and did not reach the extent of dementia. The work done shows.Conclusion. Surgical removal of all metastases in patients with multiple brain metastases provides a prognosis similar to that of patients undergoing surgery for single metastasis. Removal of symptomatic metastasis in patients with multiple cerebral lesions in most cases leads to a regression of neurological symptoms and makes it possible to continue treatment with a group of patients whose condition was considered incurable. The percentage of local relapses in the removal of multiple cerebral metastases, subject to oncological principles, is the same as in the removal of single metastases.